Addressing Challenges in Research Aimed at Reducing Financial Toxicity Among Cancer Patients and Caregivers: An Example From the CREDIT Study (SWOG S1912CD) - Ari Bell-Brown MPH; Bernard Tawfik MD; Babara Segarra-Vazquez MT, DHSc; Talor Hopkins MPA; Kate Watabayashi BA; Patricia O’Kane BS; Ruth C. Carlos MD, MS; Shelby L. Langer PhD; Joseph M. Unger PhD; Amy K. Darke MS; Dawn L. Hershman MD, MS; Scott D. Ramsey MD, PhD; et al. (Cancer Control)
Introduction Cancer-related financial hardship is pervasive, impacting both patients and caregivers, making it crucial to address financial hardship at the household level. The CREDIT (S1912CD) study was designed to enroll and randomize cancer patients and spousal caregivers as dyads to proactive financial navigation compared to usual care. The study faced several challenges to recruitment. This paper discusses the changes made to successfully complete the study. Methods The study took place among NCI Community Oncology Research Program (NCORP) sites and allowed several venues for protocol feedback, including SWOG group meetings, NCORP administrator meetings, and individual calls with recruiting sites. A patient advocate worked with the study team to review and update documents to ensure the study was relevant and accessible to potential participants. Results Several barriers were identified including sites facing challenges in enrolling patient-spouse dyads, multiple financial navigation partners causing confusion and delays in delivery of the intervention, eligibility criteria concerns, and participant discomfort with providing social security numbers. Several modifications were made to address these obstacles during a study restructure, including making caregiver participation optional, streamlining intervention delivery, and modifying eligibility criteria to allow more time between diagnosis and enrollment. Changes from the restructure resulted, on average, in a 9.5 patient per month increase in accrual (4.1 to 13.6) and has enabled the study to reach overall accrual within the study timeline. Importantly, the study maintained diverse accrual and continued to accrue willing caregivers to enable exploratory analysis of caregiver outcomes. Conclusion Interventions examining how to mitigate financial hardship for cancer patients and those affected by cancer, must be pragmatic in order to be translated into sustainable programs in real world settings. Providing recruiting sites an avenue for feedback ensured that the study team could adjust the protocol to meet site needs and successfully complete this financial navigation study.